2019
DOI: 10.3389/fpsyt.2019.00389
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Machine Learning to Detect Personality Faking-Good in a Male Sample: A New Model Based on Minnesota Multiphasic Personality Inventory-2 Restructured Form Scales and Reaction Times

Abstract: Background and Purpose. The use of machine learning (ML) models in the detection of malingering has yielded encouraging results, showing promising accuracy levels. We investigated the possible application of this methodology when trained on behavioral features, such as response time (RT) and time pressure, to identify faking behavior in self-report personality questionnaires. To do so, we reintroduced the article of Roma et al. (2018), which highlighted that RTs and time pressure are useful variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 52 publications
4
28
1
2
Order By: Relevance
“…On the one hand, honest respondents remained honest under the speeded condition, indicating that they were not affected by time pressure; on the other hand, faking-good respondents in the speeded condition did not show the expected significant increase in T-scores. This result does not exactly agree with the findings of previous studies 17,22,23 , demonstrating that a speeded condition induces fakers to significantly improve their self-presentation (as demonstrated by increased T-scores) relative to an unspeeded condition, on both the MMPI-2-RF L-r and K-r scales 17 and the MMPI-2 L and K scales 23 . The authors of these studies suggested that time pressure may limit respondents' ability to consider the appropriateness of endorsing particularly virtuous items, and this may lead them to enhance their positive self-presentation and subsequently present less believable profiles.…”
Section: T-scores On the Mmpi-2 Underreporting Scales (L K S) And Tcontrasting
confidence: 90%
See 2 more Smart Citations
“…On the one hand, honest respondents remained honest under the speeded condition, indicating that they were not affected by time pressure; on the other hand, faking-good respondents in the speeded condition did not show the expected significant increase in T-scores. This result does not exactly agree with the findings of previous studies 17,22,23 , demonstrating that a speeded condition induces fakers to significantly improve their self-presentation (as demonstrated by increased T-scores) relative to an unspeeded condition, on both the MMPI-2-RF L-r and K-r scales 17 and the MMPI-2 L and K scales 23 . The authors of these studies suggested that time pressure may limit respondents' ability to consider the appropriateness of endorsing particularly virtuous items, and this may lead them to enhance their positive self-presentation and subsequently present less believable profiles.…”
Section: T-scores On the Mmpi-2 Underreporting Scales (L K S) And Tcontrasting
confidence: 90%
“…To conclude, this exploratory study suggests that some parameters of mouse dynamics-especially velocity on the x-axis-could be useful for detecting subjects who fake good when completing the validity scales of the MMPI-2 and PPI-R personality questionnaires, independent of whether a time pressure condition is imposed. However, upon comparing the accuracy performance obtained in this study (72-80%) with the accuracies reported in previous studies, it seems that mouse parameters may be less accurate than simple RT analysis (with reported accuracy ranging from 75-95%) 22 for this task. The present findings are still preliminary and confirmatory studies are needed.…”
Section: Effect Of Time Pressure On Mouse Movements and Trajectoriessupporting
confidence: 46%
See 1 more Smart Citation
“…One such method is supervised machine learning (ML), an area of artificial intelligence concerned with the development of algorithms and techniques able to automatically extract information from the available data. In recent years, it has been shown that psychometric testing may be augmented using ML techniques (20) in different fields application, amongst others in neuroimaging (21), malingering (22,23), genetics (24), and clinical medicine (25). As far as we know, this is the first time that such methods have been applied to fibromyalgia and related psychological domains of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Many methodologies and techniques have been developed for detecting response distortion over the years, for example, machine learning models, reaction times, regression analysis, etc. (Dunn et al, 1972;Sellbom and Bagby, 2010;Jiménez Gómez et al, 2013;Monaro et al, 2018;Roma et al, 2018;Mazza et al, 2019). Still, there is a concern about the perceptions and interpretations of the change on items due to intentional dissimulation.…”
Section: Introductionmentioning
confidence: 99%